The whole-body microbiome : how to harness microbes-inside and out-for lifelong health - Finlay, B. Brett, 1959-; Finlay, Jessica M. (The Experiment, 2019)
"Explores the role that the human microbiome (including, but not limited to, the gut) plays in aging. Includes emerging research and personal health tips"--